An Armenian Mediterranean
XXI, 337 p. 19 illus., 10 illus. in color.
Keywords: This book rethinks the Armenian people as significant actors in the context of Mediterranean and global history. Spanning a millennium of cross-cultural interaction and exchange across the Mediterranean world, essays move between connected histories, frontier studies, comparative literature, and discussions of trauma, memory, diaspora, and visual culture. Contributors dismantle narrow, national ways of understanding Armenian literature; propose new frameworks for mapping the post-Ottoman Mediterranean world; and navigate the challenges of writing national history in a globalized age. A century after the Armenian genocide, this book reimagines the borders of the “Armenian,” pointing to a fresh vision for the field of Armenian studies that is omnivorously comparative, deeply interconnected, and rich with possibility.